Observed and Normative Discount Functions in Addiction and other Diseases - Cruz Rambaud, Salvador; Muñoz Torrecillas, María J.; Takahashi, Taiki (Frontiers in Pharmacology, 2017)
The aim of this paper is to find a suitable discount function able to describe the progression of a certain addiction or disease under treatment as a discounting process. In effect, a certain indicator related to a disease whose curve decays over time in a manner which is mathematically similar to the way in which discounting has been modelled. The discount functions observed are analyzed in experiments which study addictive and other problematic behaviors as well as some alternative hyperbola-like discount functions in order to fit the patience exhibited by the subject after receiving the treatment. Additionally, it has been experimentally found that people with addiction display high rates of discount (impatience) and preference reversals (dynamic inconsistency). This excessive discounting must be correctly modelled by a suitable discount function, otherwise, it can become a trans-disease process underlying addiction and other disorders. The (generalized) exponentiated hyperbolic discount function is proposed to describe the progression of a disease with respect to the treatment, since it maintains the property of inconsistency by exhibiting a decreasing discount rate after an initial period in which the opposite occurs.